IDENTIFIKASI METABOLIT SEKUNDER DAN UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK DAUN SAMBUNG NYAWA (Gynura procumbens (Lour.) Merr). - Ferdinal, Norman; Seprianti, Lusi; Afrizal, A. (Jurnal Kimia Unand, 2023)
Sambung nyawa (Gynura procumbens (Lour.) Merr) is one of the plants used in traditional medicine. This has life-saving properties such as preventing polyps, dysentery, hypertension, diabetes, and cancer. In this study, the secondary metabolite content and antioxidant activity of sambung nyawa leaf extract were tested and its antioxidant activity. The extraction process was carried out by multilevel maceration using three different solvents, starting with hexane, ethyl acetate, and methanol. Secondary metabolite content test results showed that ironwood leaves contain flavonoids, phenolics, steroids, terpenoids, and alkaloids. The result of the antioxidant activity test using the DPPH method (1,1-Difenil-2- pikrilhidrazil) showed that the methanol extract showed very strong activity with an IC50 value of 15,01 mg/L, while the ethyl acetate showed moderate antioxidant activity with an IC50 value of 147,04 mg/L, and the hexane extract showed antioxidant activity with an IC50 value of 361,66 mg/L.